Portable hand‐held bioprinters promote in situ tissue regeneration - Zahra Pazhouhnia; Nima Beheshtizadeh; Mojdeh Salehi Namini; Nasrin Lotfibakhshaiesh (Wiley, 2022)
Abstract Three‐dimensional bioprinting, as a novel technique of fabricating engineered tissues, is positively correlated with the ultimate goal of regenerative medicine, which is the restoration, reconstruction, and repair of lost and/or damaged tissue function. The progressive trend of this technology resulted in developing the portable hand‐held bioprinters, which could be used quite easily by surgeons and physicians. With the advent of portable hand‐held bioprinters, the obstacles and challenges of utilizing statistical bioprinters could be resolved. This review attempts to discuss the advantages and challenges of portable hand‐held bioprinters via in situ tissue regeneration. All the tissues that have been investigated by this approach were reviewed, including skin, cartilage, bone, dental, and skeletal muscle regeneration, while the tissues that could be regenerated via this approach are targeted in the authors' perspective. The design and applications of hand‐held bioprinters were discussed widely, and the marketed printers were introduced. It has been prospected that these facilities could ameliorate translating the regenerative medicine science from the bench to the bedside actively.